Management of a parotid sialocelein a young patient: case report and literature review - Melissa Rodrigues de Araujo (Journal of Applied Oral Science, 2010)
Sialocele is a subcutaneous cavity containing saliva, caused by trauma or infection in the parotid gland parenchyma, laceration of the parotid duct or ductal stenosis with subsequent dilatation. It is characterized by an asymptomatic soft and mobile swelling on the parotid region. Imaging studies are useful and help establishing the diagnosis, such as sialography, ultrasonography, computed tomography and magnetic resonance imaging. This paper describes a recurrent case of a parotid sialocele in a young female patient. She presented a 6 cm x 5 cm swelling on the left parotid region. The ultrasonographic scan of the area revealed a hypoechoic ovoid well defined image suggesting a cyst. A sialography of the left parotid showed a cavitary sialectasia in a panoramic and anteroposterior view. A conservative management was adopted by percutaneous needle aspiration of the swelling, which was useful to provide material for analysis and helped healing. Dentists should be aware of this pathology and the importance in adopting a conservative treatment whenever it is possible.